THE LEGAL PROTECTION OF CONSUMERS FOR ACQUISITION PDAM CLEAN WATER SERVICE (The Case Study Of PDAM Surabaya City) - Dewi, Rista Veria; Djulaeka, Djulaeka (Faculty of Law Universitas Trunojoyo Madura, 2020)
This study was conducted to determine the existence of negligence on the quality standard of water that is flowed by PDAM Surya Sembada, as well as legal remedies that can be carried out by consumers who suffer losses from the clean water services they receive. The research method used is normative research. The research approach is was carried out using a legislative aprroarch, namely by reviewing the law in accordance with legal issues raised related to water quality standards and the responsibilities of PDAM Surya Sembada as the service provider of clean water service recipients in the Surya Sembada City PDAM Surabaya as a cunsumers. The results showed that the service recipient felt disadvantaged, because there were several aspects of the quality standard of water that was flowed as reflected in the provisions of Permenkes No. 492 of 2010 concerning Requirements for Drinking Water Quality that were not appropriate and the provision of compensation by clean water service providers to the recipients of services whose right have been impaired is also not carried out properly, so that consumers as service recipients can file claims related to compensation suffered through out of court (no litigation) and court (litigation) ways.